Impact of Reward System on Academic Staff Engagement (ASE) and Organisational Performance (OP) in Technical Universities (TUs): A Case of Ghana - Davis, Marian S; Okeke-Uzodike, Obianuju (Journal of Management and Research, 2024)
Reward systems are significant organisational management tools for acquiring, retaining, and motivating potential employees and for attaining higher levels of performance. The primary goal of this research is to explore the impact of reward system on academic staff engagement and organisational performance in selected Technical Universities (TUs) in Ghana. To achieve the objective, data was collected using Google Forms from 315 academic staff working at 5 selected TUs. Afterwards, it was gathered in SMART PLS (SEM) and analyzed using descriptive and inferential statistics. The findings revealed that (i) Academic Staff Engagement (ASE) has a significant positive effect on Reward System (RS), (ii) RS has a significant positive effect on Organisational Performance (OP), (iii) ASE influences OP, and (iv) RS significantly mediates the relationship between ASE and OP. Therefore, the findings suggested that the organisational reward system and academic staff engagement are critical human resource factors for improving the performance of the technical institutions. The outcome of this research calls for the policy makers and the TUs management to consider reward system and academic staff engagement programs as tools for driving institutional performance. The study also contributes significantly to the knowledge and the application of ASE, RS, and OP in theory and practice in the context of higher education institutions.